The apprehensiveness of Malaysian citizens towards the covid-19 virus vaccine / Ainur Zamratul Fatihah Abd Rahim … [et al.] - Abd Rahim, Ainur Zamratul Fatihah; Muhammad Radzi, Chut Alysha; Mohd Ketar, Muhammad Azizul Azeem; Ridzuan, Abdul Rauf; Ramlan, Aini Faezah (Faculty of Communication & Media Studies, 2021)
Apprehensive brings the definition of one being anxious or fearful that something bad or unpleasant will happen to them. Humans are bound to feel concerned and apprehensive towards something new and uncommon to the public’s eye. In correlation with the COVID-19 pandemic that is currently ongoing, the study is aimed to study the level of concern towards the COVID-19 vaccine and to determine the levels of apprehensiveness towards the COVID-19 vaccine. We distributed an online questionnaire to support the study consisting of 13 items in the demographic section and another 24 questions to measure the level of apprehensiveness and curiosity of our fellow Malaysian citizens. The study incorporated 475 respondents from all over Malaysia through the Google Form platform. All variables were measured through scales previously used by other researchers. All of the factors were assessed using scales that have previously been utilised by other studies. Based on the Krejcie and Morgan Table, N=475, S=210, the survey amount was determined. The analysis was conducted using SPSS ver. 20 software, and the findings of the spss suggested that our respondents are quite curious (81.9%) and a little over half of the respondents are apprehensive (53.9%).